A broader lens on tuberculosis cost-effectiveness analysis : How patient-incurred costs and post-tuberculosis outcomes reshape estimates in a multi-country study - Tomeny, Ewan M; Tran, Phuong Bich; Kazibwe, Joseph; Rosu, Laura; Nikolaidis, Georgios F; Nightingale, Rebecca; Wingfield, Tom; Meghji, Jamilah; Squire, S Bertel; Worrall, Eve (PLOS global public health, 2025)
Tuberculosis (TB) remains a major public health challenge, with financial and health impacts extending beyond treatment. Both the perspective adopted in cost-effectiveness analyses-which critically determines choices such as the inclusion of patient-incurred costs-and the extent to which long-term post-treatment considerations are incorporated have important policy implications. This study examines how the choice of timeframe and cost perspectives influence the estimated cost-effectiveness of TB interventions, particularly preventative measures. Using data from 19 WHO TB patient cost surveys and global epidemiological databases, we modelled a hypothetical preventative TB intervention, generating four incremental cost-effectiveness ratios (ICERs) per country under different analytical approaches. These included a conventional timeframe up to treatment completion, an extended timeframe incorporating post-TB effects, and two perspectives that either included or excluded patient-incurred costs. The approach yielding the lowest ICER (societal perspective; extended timeframe) was anchored in the primary analysis to a 1×GDP per capita threshold. Using this benchmark simplified cross-country comparisons and removed the need for health system cost estimates. Sensitivity and scenario analyses explored how threshold values influenced the relative impact of timeframe and costing perspective. ICERs were higher when patient costs were omitted or the post-TB period was excluded, peaking when both were absent. However, across all countries, post-TB considerations had a far greater impact on cost-effectiveness. On average, removing the post-TB period increased ICERs by over 50% (ranging from +19.3% in Ghana to +108% in Mongolia, societal perspective). Including patient-incurred costs increased the likelihood that prevention was cost-effective, particularly in low-GDP settings with lower willingness-to-pay thresholds. However, their impact was minimal above 2×GDP. Our study highlights how narrowly defining the financial and health burden of tuberculosis in cost-effectiveness analyses risks underestimating the benefits of interventions-particularly in lower-GDP countries where the socioeconomic burden of tuberculosis is greatest-which could lead to misguided policy decisions that overlook the full impact of tuberculosis.
Copyright: © 2025 Tomeny et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.